The behaviour of an arrow shot from a compound archery bow - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2011)
The behaviour of an arrow exiting an archery bow is of interest in relation to equipment selection and optimization, as well as to the performance of the arrow down-range. In particular, it is a necessary input into a study of the impact of archer technique errors and wind drift. While the performances of recurve archery bows have been modelled by a number of researchers, those of compound archery bows have not. A compound archery bow is mechanically more complex and the archer holds the string using a mechanical release device rather than with fingers directly on the string. Consequently the arrow behaviour is significantly different from that for a recurve bow.